A Systematic Review and Meta‐Analysis Comparing Heterogeneity in Body Mass Responses Between Low‐Carbohydrate and Low‐Fat Diets. Issue 10 (22nd September 2020) - Smith, Eleanor S.; Smith, Harry A.; Betts, James A.; Gonzalez, Javier T.; Atkinson, Greg
Abstract : Objective: An important notion in personalized medicine is that there is clinically relevant treatment response heterogeneity. Low‐carbohydrate (CHO) and low‐fat diets are widely adopted to reduce body mass. To compare individual differences in responses between two dietary interventions, a formal statistical comparison of response variances between study arms in a randomized controlled trial (RCT) is crucial. Methods: The change in variances in RCTs for the body mass responses to low‐CHO dietary interventions versus change variances for the low‐fat groups (typically considered as the comparator intervention) were compared. A literature search identified relevant RCTs ( n  = 25; 3, 340 participants). The means and SDs of body mass change in low‐CHO and low‐fat study arms were extracted to calculate the variances of individual responses. These were meta‐analyzed in a random‐effects model and converted to the SD for individual responses. Results: The pooled SD for individual responses for body mass was 1.4 kg (95% CI: −1.1 to 2.3) with a wide 95% prediction interval of −6.3 to 10.4 kg. Conclusions: Evidence is insufficient to suggest the response heterogeneity to low‐CHO diets differs from that observed with low‐fat diets.